(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The Age of Enlightenment was a movement of philosophy that dominated Europe’s sphere of ideas. This movement advocated ideals like as freedom, progress, compassion, brotherhood, constitutional rule, church and state separation, all based on the concept that reason is the primary source of authority and legitimacy. The precise beginning of such an age of enlightenment is under discussion, while the beginnings of the 18th century (1701) are often mentioned as starting points, even in the mid-19th century (1650). According to French historians, the period is usually between 1715 and 1789. The end of the Enlightenment was usually the result of many historians until the latter years of the siècle; generally, the French Revolution began in 1789, or the Napoleonic War (1804– 15). The Enlightenment was generally adopted by most European countries with a regional emphasis. Cultural contact between particular European countries and across the Atlantic had occurred in both ways throughout Age of Enlightenment. In the discussion and thought about illumination, science started to take center stage. The Enlightenment was long regarded by Western civilizations as the intellectual and political foundation. It was in charge of the political modernization of the West. Concerning religion, the critique of the Enlightenment era has responded to the European religious struggle of the last century. The researchers have reviewed the relevant studies on the Age of Enlightenment and determined that, by living in the present moment in the future, their knowledge of life and the world around it may be enlightened and expanded.